Addressing Digital Content Fraud and Ethical Monetization: from the DSN-MUI Perspective - Mubarok, Jaih; Rahmat; Rosyadi, Imron; Yayuli; Elvri, Rini (Indonesian Journal of Islamic Economic Law, 2026)
This study aims to reinterpret the methodology of the Indonesian Ulema Council's National Sharia Board (DSN-MUI) Fatwa No. 62/2007 on Ju'alah and Fatwa No. 116/2017 on Sharia Electronic Money in the context of the modern digital economy, particularly in dealing with the phenomenon of content fraud on monetisation platforms such as TikTok. Using a qualitative approach, this study employe Islamic legal analysisto assess how the Ju'alah contract can shift from a normative-individual interpretation to a socio-structural understanding. The results of the study show that the reinterpretation of the two fatwas expands the function of the Ju'alah contract into a digital ethical and legal framework that emphasises justice, trust, transparency, and collective responsibility between creators, platforms, and regulators. The integration of Sharia principles with modern technologies such as blockchain, traceability systems, AI transparency, and homomorphic encryption enables the creation of an accountable digital monetisation system that is free from elements of gharar, tadlīs, and maysir. This study also confirms that the implementation of maqāṣid al-syarī‘ah values can form the basis for the establishment of a fair and sustainable digital economic governance system. However, this research is still conceptual and requires further empirical validation through algorithmic audits and the development of Sharia smart contracts. The results of this study are expected to be an important contribution to the development of a digital Islamic economic paradigm that is adaptive to technology, while remaining based on the principles of justice and public benefit.